1997
DOI: 10.1002/(sici)1097-4628(19970725)65:4<685::aid-app7>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin release behaviors from pH and thermoresponsive poly(vinyl alcohol) and poly(acrylic acid) IPN hydrogels for site-specific drug delivery

Abstract: A temperature-and pH-responsive drug delivery system was studied by using interpenetrating polymer network (IPN) hydrogels constructed with poly(acrylic acid) (PAAc) and poly(vinyl alcohol) (PVA). The release of indomethacin incorporated into these hydrogels showed pulsatile patterns in response to both pH and temperature. Indomethacin diffused from the polymer matrices through the swelling and deswelling mechanism. The release amount increased at higher temperature because of the swelling caused by the dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Specifically, this requires the polymerization of both networks simultaneously and results in two intermixed networks that can only be separated by breaking bonds. These materials are of interest due to their ability to introduce new properties when the networks interact [95,96] or two different properties when acting independently.…”
Section: Interpenetrating Networkmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, this requires the polymerization of both networks simultaneously and results in two intermixed networks that can only be separated by breaking bonds. These materials are of interest due to their ability to introduce new properties when the networks interact [95,96] or two different properties when acting independently.…”
Section: Interpenetrating Networkmentioning
confidence: 99%
“…In contrast to the studies discussed above, where the drug release was slowed by the temperature increase, Shin et al demonstrated a hydrogel with a positive thermoresponse, i.e., drug release increases with increasing temperature [95]. Specifically, an interpenetrating network of polyacrylic acid (PAA) and polyacrylamide (PAAm) forms hydrogels that swell above their upper critical solution temperature, UCST, due to hydrogen bonding between the two different networks being disrupted at higher temperatures allowing the networks to swell [95].…”
Section: Interpenetrating Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…The unique properties of a smart hydrogel imply that it can be used as a promising material in the biomedical and industrial applications. Some significant applications of hydrogels have been widely investigated including dialysis membranes [11], enzyme immobilization [12], tissue engineering [13], and drug controlled release systems [14][15][16][17] and so on. Among the smart materials, pH-and temperature-sensitive hydrogels have been paid more attentions because the two physiological factors are very important for the human body [18][19][20][21].…”
Section: Introductionmentioning
confidence: 97%